Impact of organizational justice perceptions and transformational leadership role on counter productive work behavior - Yogasari, Ida Ayu Mahesta; Budiasih, I Gusti Ayu Nyoman (International research journal of management, IT and social sciences, 2019)
This study examines the impact of organizational justice perceptions and transformational leadership role on counterproductive work behavior. The study illustrates that organizational justice (procedural and interactional justice) perception and transformational leadership produces a negative impact on counterproductive work behavior (organizational and interpersonal). The reduction utilizes social exchange theory. Survey methods and purposive sampling methods was conducted by collecting primary data from respondents working as an accounting team member in the Food and Beverage sector of the Badung Regency. The primary data were processed with a multiple linear regression model. Survey results reveal that procedural justice and interactional justice as well as transformational leadership significantly impact counterproductive work behavior (organizational and interpersonal).